ANALISIS PENYUSUNAN ANGGARAN DAN LAPORAN REALISASI ANGGARAN PADA BADAN PENGELOLAAN KEUANGAN DAN PAJAK DAERAH KOTA SURABAYA - Taufiq, Taufiq Hidayat1969 (Majalah Ekonomi, 2022)
ABSTRACT This study aims to identify and analyze the budget preparation process and budget realization reports, find out, analyze what obstacles are faced in the budget preparation process, find out and analyze what efforts are being made to overcome obstacles in budgeting at the Badan Pengelolaan Keuangan dan Pajak Daerah (BPKPD). City of Surabaya during the 2018 - 2019 fiscal year. The method used in this study is a qualitative descriptive research method. In carrying out this research, this research takes primary data obtained from budgeting and program staff, and the data collection is carried out by the authors conducting interviews and documentation involving informants, namely the Budget Sector, Sub-Division of Budgeting and Sub-Sector of Budgeting System, Badan Pengelolaan Keuangan dan Pajak Daerah (BPKPD). City of Surabaya . Based on the results of the study, it can be concluded: Judging from the implementation process, the overall budget preparation is in accordance with Permendagri Number 33 of 2017 and Permendagri Number 38 of 2018. The implementation of the budget program at the Surabaya City Regional Tax and Financial Management Agency for the two 2018 and 2019 fiscal years according to PMK No.249/PMK.02/2011 as a whole is included in the criteria quite well, In the 2018 budget year the budget realization report obtained the results of the Income variant 107.22% (Very Good), Original Regional Revenue 108.22% (Very Good), Transfers Revenue 96.42 % (Very Good), Other Legal Financial 121.11% (Very Good) Expenditure 112.05% (Very Good) Operational Expenditure 111.74% (Very Good) Capital Expenditure 113.34 % (Very Good) Unexpected Expenditure25.88% (Poor), Fiscal year 2019 Revenue 100.37% (Very Good), Local Revenue 102.81% (Very Good), Transfer Revenue 104.46% (Very Good), Others To Legal money 121.11% (Very Good) Spending 92.24% (Very Good) Operational Expenditure 91.55% (Very Good) Capital Expenditure 92.28% (Very Good) Unexpected Spending 11.88 % (Poor) Keywords: Budgeting and Budget Realization Report.